Pengaruh Partisipasi Masyarakat terhadap Pembangunan Daerah di Kecamatan Katobu Kabupaten Muna - Iwe, La; Sinaini, La (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
The objectives of this study are: (1) to determine community participation in regional development in Katobu District, Muna Regency. (2) to find out the factors that influence community participation in regional development in Katobu District, Muna Regency. The data analysis method used in this study is qualitative descriptive analysis and quantitative analysis. The results showed that the level of community participation had a very important influence on the implementation of regional development in Batalaiworu District, Muna Regency, especially in terms of the 4 dimensions of participation, namely: (1) regional development planning/formulation dimensions; (2) implementing regional development; (3) utilization of regional development results; (4) assessment of the results of regional development. Community participation provides a positive response to regional development. Realization of the implementation of regional development, both physical and non-physical development provides a positive response or good category for regional development. Some of the factors driving community participation in regional development include (1) communication factors and well-structured government structures from the village/village level to have a positive effect; (2) political factors and human resources become inhibiting factors in the implementation of regional development in Katobu District, Muna district.